Transformation Of High School Geography Learning: 3d Hydrological Cycle Media Training For MGMP Teachers - Helfia Ideal; Deded Chandra; Sari Nova; Sri Kandi Putri; Yulia Hanoselina; Sri Mariya; Ratna Wilis; Rana Rana; Arrahmah Dea Syamsaputri; Annisa Annisa (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
The training on developing 3D media of the hydrological cycle was conducted for geography teachers in the MGMP of SMA/MA in Pariaman City and Padang Pariaman Regency to enhance pedagogical skills and diversify instructional media. The program consisted of administrative preparation, delivery of hydrology materials, and practical sessions using a semi-prepared model strategy for efficiency. Evaluation employed Likert-scale questionnaires, observation, and group discussions. Results indicated an average satisfaction score of 4.4 out of 5, with the highest for student benefit (4.7) and the lowest for model complexity (3.8). Furthermore, 90% of teachers expressed readiness to implement the media in their classrooms. Discussions also highlighted local issues, such as the reliance on rainwater consumption, which enriched teachers’ perspectives on water quality and safety. The program was concluded to be effective in strengthening teachers’ capacities and recommended enhancing model complexity and expanding innovative media development.